Evaluation of Seismic Behavior of the Effect of Yielding Slit Dampers on Steel Beam to Column Connections (Journal of Civil Engineering Researchers, 2021)
During the Northridge and Kobe earthquakes, many steel bending frames were damaged in beam-to-column joints. Excessivedeformation due to structural stiffness and rigidity limits the use of this system. Ductility of joints causes more energy to be lostbefore joints fail. As a solution, slit steel dampers were used in the joints to prevent brittle damage to the joints and damage tothe main members of the structure. In the present study, a yielding slit damper has been validated in the laboratory using datafrom a valid article; it is done through ABAQUS finite element software. The evaluation and comparison of nonlinear andnumerical analysis of yield slit dampers will be presented hereafter. The first part of this assessment is about the vertical loadof the beam connected to the steel column, which will be followed by the evaluation of the research variables, i.e., the differentmodes of change in thickness, state and reinforcement of the slit damper, in the connection of the beam to the steel column. The results show that increasing the damper thickness increases its strength, hardness and absorbed energy but decreases its ductility. The same results also indicate that internal strengthening of a yielding slit damper in beam-to-column connections increases strength, stiffness and laterally absorbed energy but decreases the ductility. Meanwhile, the proposed specimen and idea of a yielding slit damper in the connection of the beam to the steel column, has proved that the reinforced specimen of the proposed specimen has the best performance among the specimens and transfers the plastic area into the damper range in the connection of the beam to the steel column.
Keywords: slit steel dampers; beam-to-column connections; absorbed energy; finite element